CORRELATION OF FOOT & HAND LENGTH MEASUREMENT WITH GESTATIONAL MATURITY IN NEONATES - DR.S.R.SATEESHA; DR.H.S.NIRANJAN; DR.A.S.JAGADISH; DR.NAVEEN BENAKAPPA. (International Journal of Pharma and Bio Sciences, 2015)
Anthropometric measurements serve as useful adjuncts of growth and maturity.Prospective study was conducted at tertiary care NICU to study the correlation between foot and hand length with gestational age in neonates. Foot length has significant correlation with gestational age in preterm SGA, preterm AGA and term AGA babies (p<0.05). Similarly, hand length has strong correlation with gestational age in preterm AGA and term AGA(p<0.05).Hence foot length and hand length can be used as surrogate marker for gestational age especially in community settings .However larger studies are required and specific reference charts need to be created.